Health Insurance Policies For Informal Workers: A Review For National Health Insurance - Wiwik Sriwahyuni Batubara; Darwono Darwono; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
Moral hazard in health insurance is a significant institutional issue that concerns the efficiency, sustainability, and equity of health funding systems. This study intends to comprehensively assess the different types of moral hazard, discern the root causes that contribute to it, and examine the regulatory strategies implemented at both national and international levels. This study employed a methodology characterized by a descriptive literature review, which involved a comprehensive analysis of 25 meticulously chosen peer-reviewed articles. The articles in question were published between the years 2014 and 2025, and they were obtained from reputable databases such as Scopus, PubMed, and Google Scholar. The results indicate that moral hazard presents itself in two main forms. Initially, this phenomenon arises among beneficiaries who may engage in excessive consumption and use of healthcare services lacking adequate medical justification. Secondly, it is apparent that healthcare providers may participate in administrative and clinical manipulation, which includes practices such as upcoding, unnecessary hospitalizations, and fraudulent claims. Several contributing factors to moral hazard can be identified, including deficiencies in the design of the INA-CBGs payment system, a lack of health insurance literacy among participants, and insufficient oversight and auditing mechanisms.The findings presented have considerable implications for policymakers, outlining the necessity to improve the national health insurance system. Structural reforms and the implementation of sustainable, multidisciplinary approaches.